Conventional vs. Organic Agriculture–Which One Promotes Better Yields and Microbial Resilience in Rapidly Changing Climates? - Azarbad, Hamed (Frontiers in Microbiology, 2022)
In recent years, agricultural productivity has been affected dramatically by climate-related events such as drought. On the other hand, agricultural intensification is expected to increase to satisfy the need for increased global food production. Microbes associated with soil and plants produce a range of bioactive natural products that significantly contribute to crop stress tolerance. Therefore, a better understanding of the parallel effects of agricultural management (conventional and organic croplands) and climate conditions on soil-microbe-plant interactions is crucial to maximizing the effort in engineering a plant microbiome that can better support productivity in agroecosystems. This paper provides a general overview of the major current debates on conventional and organic farming performance regarding yields, particularly under ambient and future climate conditions. With the main focus on cropland, the effect of agricultural management on soil and plant microbiomes is discussed. In addition, the advantage of incorporating microbiome-based approaches into current farming practices to ensure agricultural productivity with less adverse environmental impacts is highlighted. To enhance crop production under organic farming without massive land-use changes and expansion of farmland, the microbial-based approach can be used to ensure higher productivity, particularly under a rapidly changing climate.